Strategy for Reducing Regional Economic Disparities in Gerbangkertosusila: A Cluster Regional Approach Based on Leading Sectors - Belia Fransiska; Edi Setiawan (Department of Urban and Regional Planning, Diponegoro University, 2022)
The existence of regional clusters has a favourable influence on the prosperity and development of a region. Regional clusters have the potential to create a conducive environment that encourages businesses to develop. In addition, they promote regional growth and development; therefore, those regions provide trickle-down effects to the surrounding. Gerbangkertosusila (GKS), as a metropolitan area, has an important role in the economic development of East Java Province because had several economic activities. However, in fact, the economic development in the GKS area is uneven and results in inequality. Furthermore, the changes in the aspect of regional economic development had also not balanced with the formulation of appropriate policies. Therefore, this paper aims to propose strategies to reduce the regional economic disparities in the GKS area. The analysis will use Williamson Index to determine regional inequality and LQ (Location Quotient) to determine the performance of each sector. From the analysis results, we offer some strategies based on the leading sectors and regional competitiveness there that was: 1. Strategies based on natural resource management and local economic development in cluster A (Lamongan and Bangkalan Districts) that have advantages in resource endowment; 2. Strategies to strengthen the productive business environment and environmentally friendly industries that are interrelated in cluster B (Sidoarjo, Gresik, and Mojokerto districts); 3. Strategy based on optimization of urban roles and functions supported by the development of human resources and the development of the creative economy in cluster C (Mojokerto City and Surabaya City).